Analisis Pengendalian Kualitas Dengan Metode Statistical Process Control (SPC) Dalam Upaya Mengurangi Tingkat Kecacatan Produk Pada PT. Gaya Pantes Semestama - Riadhy Sanjaya Hidayat (Magister Manajement Studies Program, 2022)
Quality is the features and characteristics of product or service that have the ability to fulfill the consumers’ needs today and in the future. Quality control is a technique and planned activity. The aim of this activity is to achieve, maintain, and increase the quality of product or service to equal the standard and fulfill consumer satisfaction. This research aims to know the description of the production process, examines the factors that lead to the failure of the product, find out the actions that should be done by the company to reduce the level of defects on their production. PT. Gaya Pantes Semestama engaged in the fabric industry. This research used the descriptive and analysis method that used is Statistical Process Control in the form check sheet, Pareto diagram, fishbone, and P-Chart. From the result of the research, the main factors causes the defects are human, machine, raw material, and work environment. Keywords: Quality Control, Statisitical Process Control, Check Sheet, Pareto Diagram, Fishbone, P-Chart